INVESTIGATION OF THE IONIZED COMPONENT OF THE LOCAL INTERSTELLAR MEDIUM - Bochkarev, N. G.; Ryabov, M. I.; Isaeva, E. A. (Одеські астрономічні публікації, 2017)
Based upon numerous observational data of variability in extragalactic radiosources of the southern sky at low frequences the possibility of obtaining information on ionized component structure in the Local Interstellar Medium (LISM) is investigate. The model of anisotropic structure of LISM developed by Bochkarev (1987) is compared with investigational results of extragalactic radio sources scintillation of the southern sky at 80 and 160 MHz (Slee, Siegmen, 1988). In the direction where scintillation indices increase, regions of interaction of interstellar wind with large scale structure of LISM are located. Decrease region of scintillation indices are observed wherein on towards the third galactic quadrant (near l = 240°), there is a gas free tunnel. On the basis of the theory refraction scintillation the estimations of characteristic time of changes of flows of radiosources on frequency 100 MHZ for the mentioned above areas LISM are considered. In view of high importance of speed of movement inhomogenius of electronic concentration and their sizes for the given areas LISM, reaching 500 km/sec and 20-70 a.u., the characteristic times variability turn out equal 0.1-0.7 years, that will be coordinated to the data of supervision.